The Effect of Overprotective Parental Attitudes on Children's Development - Andini Hukma Salmin; Dian Nasrudin; Muhammad Sandi Hidayat; Wiwin Winarni (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2021)
This study aims to describe how good parenting patterns affect their children. Later in the study described how it characterizes overprotectivebehavior, the factors that influence overprotective attitudes of parents as well as the impact that overprotective parenting patterns have on their children. This research method uses qualitative approach with descriptive research methods and surveys. The study used several respondents. The ways to carry out this research used by researchers are observations, interviews, and documentation. The results of this study show that overprotective attitudes of parents are a form of excessive parental protection given because they are afraid if their child happens things that are not wanted. But the overprotective attitude of parents or pampering their children makes the child unable to express himself in his social environment. And the overprotective attitude of parents that will have an impact on the social development of the child is that the child has difficulty adapting to the new environment, prefers to play alone, and results in the child is not independent